Treatment of autosomal recessive and autosomal dominant polycystic kidney disease - E. F. Andreeva (Rossijskij Vestnik Perinatologii i Pediatrii, 2019)
The article reflects the genetic variants of polycystic kidney disease, describes the modern strategy for the treatment of polycystic kidney disease in children and adults. The authors present the results of clinical trials of vasopressin V2 receptor antagonists (tolvaptan, liksivaptan), a multi-kinase inhibitor (tezevatinib), somatostatin analogues (lankreotide, octreotide), statins (pravastatin), mTOR inhibitors (everolimus, sirolimus), metformin in patients with autosomal recessive and autosomal polycystic kidney disease. The authors discuss the factors determining the prognosis and outcome of these diseases.